Alternaria vignae sp. nov. (Ascomycota: Pleosporaceae) from Vigna unguiculata in China - Huang, Cheng Xin; Liu, Feng Yin; Gou, Ya Nan; Deng, Jian Xin; Li, Mei Jia (Phytotaxa, 2022)
Alternaria is a widely distributed fungal genus served as saprophytes, endophytes and pathogens. An Alternaria species was isolated from Vigna unguiculata in Inner Mongolia Autonomous Region of China. The strains were determined based on morphological characteristics and multi-locus phylogenetic analyses including the internal transcribed spacer of rDNA region (ITS), glyceraldehydes-3-phosphate dehydrogenase (GAPDH), RNA polymerase second largest subunit (RPB2) and translation-elongation factor 1 alpha (TEF1). The results indicated that it was a new species, which described and illustrated as Alternaria vignae sp. nov. in this study. Phylogenetic analyses showed that the species formed a well-supported clade (sect. Helianthiinficientes) close to A. helianthiinficiens.